Syntheses, spectroscopic study and X-ray crystallography of some new phosphoramidates and lanthanide(III) complexes of N-(4-nitrobenzoyl)-N′, N′′-bis(morpholino)phosphoric triamide - Gholivand, Khodayar (2010)
New phosphoramidates with the formula RC(O)N(H)P(O)X2, R = 2-NO2-C6H4, 3-NO2-C 6H4 and 4-NO2-C6H4, X = N(CH2CH3) (1)-(3), NC4H8 (4)-(6), and NC 4H8O (7)-(9) were synthesized and characterized by 1H, 13C, 31P NMR and IR spectroscopy, and elemental analysis. The reaction of (9) with hydrated lanthanide(III) nitrate leads to ten-or nine-coordinated complexes, (10)-(13). The crystal structure has been determined for (3), (5), (9), (10) and (13). In contrast to all of the previously reported similar phosphoramidate compounds, the-C(O)-N(H)-P(O) skeleton in the free ligand (9) shows a cisoid conformation, with the C=O and P=O double bonds adopting a nearly syn conformation. Quantum chemical calculations were applied for clarifying this exceptional conformational behavior. The monodentate neutral ligand (9) is coordinated to the metal ions via the phosphoryl O atom, adopting the usual anti conformation between the C=O and P=O groups. © 2010 International Union of Crystallography Printed in Singapore - all rights reserved.